1983
DOI: 10.1046/j.1537-2995.1983.23183147295.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐citrate‐dextrose‐phosphoenolpyruvate medium as a rejuvenant for blood storage

Abstract: Stored, depleted RBC were rejuvenated with respect to their levels of adenosine triphosphate (ATP), 2,3-diphosphoglycerate (2,3-DPG), and P50 by acid-citrate-dextrose perservatives containing phosphoenolpyruvate (PEP) without sucrose. The restorations of P50 and 2,3-DPG were dependent on the phosphoenolpyruvate concentration. Erythrocyte P50 and 2,3-DPG, even after treatment with these preservatives, decreased with increasing storage period, but the P50 and 2,3-DPG of five-week-old blood were still higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, even though abnormal RBC shapes were seen, one study reported that the morphological changes after thawing using HES recovered rapidly in fresh autologous plasma [21]. Further research is required to determine the effects that ATP and 2,3-DPG have on RBC membranes using rejuventation [1,3,14,24] and to determine the biochemical changes to RBC membranes.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though abnormal RBC shapes were seen, one study reported that the morphological changes after thawing using HES recovered rapidly in fresh autologous plasma [21]. Further research is required to determine the effects that ATP and 2,3-DPG have on RBC membranes using rejuventation [1,3,14,24] and to determine the biochemical changes to RBC membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Ad ditions of chemicals such as bicarbonate [8], dihydroxyacetone [9], and phosphoenolpyruvate [10] have been tried but abandoned, often for practical or economical reasons. In recent studies [11] we have shown that a combination of half-strength citrate CPD [12] with a new additive solution for red cell suspension (RAS), inspired by the work of Meryman et al [13], results in good maintenance of BPG without loss of adenine nucleotides.…”
Section: Anticoagulants and Additive Solutionsmentioning
confidence: 99%
“…A certain 'rejuvenlating' effect appears to occur, however, 2,3-DPG level was not maintained even by this method (data not shown). A more effective reagent such a s phosphoenolpyruvate (Hamasaki et al, 1981;Hamasaki & Hirota-Chigita, 1983) or PIGPA solution (DeVenuto rt a/., 1974) may be required a t the final stage of storage to achieve this.…”
Section: Discussionmentioning
confidence: 99%